A vida nunca esteve tão insuportável: reflexões sobre o tédio contemporâneo e as músicas de rock da década de 80 - Oliveira, Adriana Aparecida Almeida de [UNESP] (2014)
Contemporaneity consists of the current time in which important changes and ongoing influences give the world new forms different from those canonized by the modernity due either to the intensification or radicalization of the modernization process or to the appearance of new process, among which those processes categorized as related to the postmodernity are also found. As per Harvey (1998), postmodernity is characterized by the association and acceptance of ephemeral things and temporary things, making the ideas of acceleration, instability, precariousness, metamorphosis, fragmentation futile, as well as other ideas that compose the human condition in the current time. In this scenario of loneliness, indifference and emptiness caused by velocity, distance from the other, and weakness of relationships, two forms of subjeticvation are highlighted: depression and boredom. The first one is largely found in the current times. However this research has pointed out boredom as a subjectivation typical of the contemporaneity due to its close relation with time, particularly as the expression of an attempt of time deceleration or protest against excessive things and a vertiginous lifestyle. Boredom is characterized by tiredness of living, depotentiation of life. The main purpose of this paper was to identify and analyze expressions of boredom in Brazilian culture, and its corpus consists of lyrics from Brazilian rock in the 80s that deal with boredom. Artistic and cultural productions are considered a safe way for capturing subjectivations emerging in a given time and space, since they act out as expression – symbolic manifestation – of human experience or the experienced reality. These cultural productions were addressed through content analysis, as per Bardin (2002). This method is quite proper for textual analysis, and it induces a systematic treatment of texts which allows the extraction of significat ...